Inteligência espiritual em contraposição à cultura normótica: os desafios do novo paradigma - Leão, Deusilene Silva de (2017)
This research intends to demonstrate that academic space may constitute in a propitious environment to people's transformation through the understanding of a spirituality that integrates sense and meaning to human being's lives. It is known that the modern academic space is focused in a normotonic education, this is, based primarily in the rational, in a fragmented, competitive and excluding way. Based on this reality, our hypothesis is that allying the intellectual dimension to spirituality will help human beings to build a path that will give them a purpose in life, in other words, that the insertion of a spiritual perspective, integrative and holistic in the academic environment can provide a transformation in the way people see themselves, others and the world. The methodology used was bibliographic analysis, and also a field survey with university graduate theology students from Pontifical Catholic University of Goias. This inquiry demonstrated that spiritual intelligence can be introduced in the academic grid and that, there are tools to this work that contribute both to human being's transformation and academic space's transformation, that begins to considerate the teaching-learning process in an inclusive way.